The role of public policy in promoting technical innovations - Conrad, Jobst (Technische Universität Dortmund, 2007)
The purpose of this article is to demonstrate and to discuss on the basis of an indepth case study the range and limitations of public policy aiming at promoting the development of regional innovation networks and clusters. This is done first by denominating main criteria, potentials and problems of a public policy promoting regional clusters (section 1), second by describing the development of the network association InnoPlanta and its major framework conditions (sections 2 and 3), third by summarizing the actor constellation of the network and the innovation pattern and market perspectives of InnoPlanta's research projects (sections 4 and 5), fourth by then pointing out the structure and role of public promotion policy in this process (section 6), fifth by comparing promotion objectives with results achieved (section 7), and sixth by drawing some conclusions concerning successful promotion policy in the case investigated and in general (section 8). As shown in the case study, the role, success or failure of public policy promoting the development of regional innovation networks and clusters depend on its favourable interaction dynamics with the existing social and economic contextual conditions. Therefore, referring to the in-depth case study of Conrad (2005), on the one hand these framework conditions are sketched in somewhat more detail, and on the other hand the article does not focus on one specific theoretical question, but tries to combine various analytical perspectives to explain the role and success of public promotion policy in the case of InnoPlanta. Consequently, this article concentrates on explaining the role of the BMBF InnoRegio program, in particular, for the development of the regional innovation network InnoPlanta, and not on this type of public promotion policy per se.
The case of the regional innovation network InnoPlanta
Science, Technology & Innovation Studies
Keywords: 300; 330